Perforated Sigmoid Diverticulitis in the Presence of Toxic Epidermal Necrolysis - P. Heye; A. Descloux; G. Singer; R. Rosenberg; T. Kocher (Karger Publishers, 2014)
Even though the incidence of toxic epidermal necrolysis (TEN) is low, it is also associated with a high mortality rate. The condition predominantly affects the skin, but may also affect the gastrointestinal tract, dramatically increasing mortality. We present a case of perforated sigmoid diverticulitis in the presence of TEN. The patient was taking medication, known to be a risk factor, and presented an affected total body surface area and temporal development similar to previously reported cases of TEN. Characteristic abdominal symptoms, however, were missing. Gastrointestinal involvement in TEN appears to be a poor prognostic factor; medical staff must therefore be alert to patients with TEN who complain of abdominal discomfort. The exact pathogenesis, however, remains unclear.